Multiple formation pathways for amino acids in the early Solar System based on carbon and nitrogen isotopes in asteroid Bennu samples - Allison A. Baczynski; Ophélie M. Mcintosh; Danielle N. Simkus; Hannah L. McLain; Jason P. Dworkin; Daniel P. Glavin; Jamie E. Elsila; Mila Matney; Christopher H. House; Katherine H. Freeman; Harold C. Connolly; Dante S. Lauretta (Proceedings of the National Academy of Sciences, 2026)
Samples collected from the carbonaceous near-Earth asteroid Bennu and delivered to Earth by NASA’s OSIRIS-REx mission contain organic molecules relevant to prebiotic chemistry. Stable isotopic measurements of extraterrestrial soluble organic matter provide critical insights into the formation pathways and alteration histories of such molecules, which hold significance for understanding the origins of life. We leverage state-of-the-art techniques for picomolar-scale isotopic analyses of amino acids in samples of Bennu and, for comparison, the carbonaceous meteorite Murchison. We report intramolecular δ 13 C values for glycine, which have not previously been measured in extraterrestrial materials; molecular-averaged δ 13 C values for amino acids, aldehydes, and ketones; and δ 15 N values for glycine, β-alanine, and D/L-glutamic acid. Intramolecular carbon isotope patterns of glycine in Bennu contrast with those in Murchison, suggesting distinct formation pathways. We explore several formation mechanisms and hypothesize that the observed glycine in Murchison formed dominantly by a Strecker-like synthesis under aqueous conditions, whereas the glycine currently found in Bennu may have formed mainly by modified radical–radical reactions in primordial ices at the cold, outer reaches of the early Solar System and retained its isotopic values throughout accretion and multiple episodes of aqueous alteration. This hypothesis is supported by the highly 15 N-enriched δ 15 N values in Bennu amino acids (+170 to 277‰). Differences in the δ 15 N values of D- and L-glutamic acid (Δ = 87‰) in Bennu affirm published reports of enantiomeric differences in meteoritic amino acids and challenge the assumption of isotopic uniformity between amino acid chiral pairs.